ANALISIS SISTEM INFORMASI AKUNTANSI PADA KOPERASI YANG SESUAI DENGAN SAK ETAP - Rosita, Ida Ayu Kade Rachmawati Kusasih & Lailatan Nugroho (Universitas Slamet Riyadi, 2015)
This study aims to determine that AIS consists of three elements, Its namely transaction is processing system, the system of financial reporting and management reporting system affect the financial statements in accordance with SAK ETAP on cooperative. The benefits of this research is to know that SIA has a role in the preparation of financial statements in accordance with SAK ETAP. The Researcher makes observations and collect data through questionnaires directly in cooperatives that meet the assessment to be sampled in the study. The data obtained will be processed, and analyzed using multiple regression techniques (multiple regression) of this study was to test the hypothesis that has been formulated. The results of the implementation of parts of the AIS study only transaction processing system has no effect on the financial statements in accordance with SAK ETAP, the financial statements of the cooperative does not require facilities, particularly in the form of software that is used in particular for the processing of transactions in accordance with SAK ETAP. While the system of financial reporting and management reporting system affect the financial statements in accordance with SAK ETAP, because its in the process of preparation of financial statements in cooperatives in the city of Surakarta has adjusted the accounting of cycle and implementation effectiveness of the management of the management supports the management report in accordance with the financial standards applicable namely SAK ETAP. The Suggestion of the researcher is according to the research that has been generated is given to the management of cooperatives should continue to follow the development of the information for any accounting standards that are applied in order to have a competitive advantage in business competition and similar businesses that increasingly stringent.Keywords: Accounting Information Systems, Transaction Processing Systems, System of Financial Reporting, Financial Statements, Cooperative, SAK ETAP.